Prescribing Pattern, Polypharmacy and Potentially Inappropriate Prescribing in Hospitalized Geriatric Patients of a Private Hospital in Nepal - Shrestha, Stuti; Sah, Kedar Prasad; Lama, Ale; Mahatara, Asmita; Shah, Ajay Kumar; Alam, Md Ishtiyaque (Indian Journal of Pharmacy Practice)
Background: According to national census 2021, Nepal has 6.01% of elderly people above the age of 65. It has been observed that there is 38.2% increase in geriatric population as compared to the previous census of 2011. Prescribing medicines to elderly increase the risk of adverse drug events as well as the chances of giving potentially inappropriate medications. The study was conducted with a goal to describe drug prescribing patterns, poly pharmacy and to measure the prevalence of potentially inappropriate medications using Beer’s criteria in hospitalized older patients of private hospitals in Biratnagar, Nepal. Materials and Methods: A retrospective cross-sectional study was done for all hospitalized elderly patients aged ≥65 years of Golden Hospital in Biratnagar. WHO core prescribing indicator and Beer’s Criteria 2019 were used to assess the prescribing pattern and potentially inappropriate prescribing with polypharmacy respectively. Study was conducted for 6 months from March 2022 to August 2022. Results: Most of the patients were in the age group of 65-74 years (74.2%) followed by the age group of 75-84 years old (21.3%). Out of the 225 patients examined, 57% were male and 43% were female. Most prescribed number of medicines per prescription was 7 and the most prescribed group of medicines were antimicrobials (26.82%) followed by cardiovascular drugs (20.63%). The number of drug prescribed in generic name was 2.97% and 55.55% of medicines were prescribed from the national essential drug list. 18.05% of the drugs prescribed were potentially inappropriate medications according to Beers Criteria. Conclusion: The study revealed the presence of potentially inappropriate medications and poly pharmacy in elderly patients. The case of prescriptions by generic names was found to be low. Safe prescribing practice with minimum use of drugs in elderly should be encouraged to reduce the high-risk adverse drug events.
Keywords: Beer’s Criteria; Core prescribing indicator; Elderly patients; Polypharmacy; Potentially inappropriate medications; Prescribing pattern